A Spatial Suitability Assessment of Maize and Tobacco in Response to Temperature and Rainfall Changes in Zimbabwe - Nkoma, Tsungai (Department of Environmental and Geographical Science, 2023)
Climate is changing, and this change poses threats to the agricultural sector. The impacts of climate are expected to become more extreme as the earth warms, and this change will affect climate suitability for different types of crops. The degree to which an increase in temperature patterns and rainfall variations will affect climate suitability for agricultural practices needs to be further understood. This can be achieved by performing a climate sensitivity analysis and contribute to informing adaptation policies and mitigation measures. This study aims to analyze the sensitivity of important crops in Zimbabwe, maize, and tobacco, in response to changes in temperature and rainfall patterns. This research paper used a sensitivity analysis of climate variables; rainfall, and temperature, using historical climate data derived from WorldClim for the period 1990-2018 to assess climate suitability. The historical climate data was used as the baseline to assess the sensitivity of maize and tobacco under a 2°C, 3°C, and 4°C temperature increase as well as a 5%, 15%, and 30% increase and decrease in annual average rainfall amount. The modified spatial climate data was computed in QGIS, and suitability was simulated using the Ecocrop model embedded in the DIVAGIS user platform. The results from this study indicated that in Zimbabwe, both crops are more sensitive to rainfall changes than to temperature changes (independently). A 5%, 15%, and 30% decline in the average rainfall will result in previously suitable areas becoming marginal, very marginal, and others unsuitable for both crops that are in agro-ecological regions I to III; i.e., provinces that include Mashonaland Central, Mashonaland West, Mashonaland East, Harare, and Manicaland. When crops are subjected to combined changes (temperature and rainfall), both crops become more sensitive. When exposed to high temperatures and low rainfall together, for instance, provinces such as Mashonaland Central, Mashonaland West, Mashonaland East, and Harare which are known as historically suitable areas for maize cultivation, will become marginal or very marginal. This change in suitability could have consequences not only on food security but also on people's livelihood and understanding the crops' sensitivity to climate changes helps support the well-being progress of the country.